Family language policy and homescapes among multilingual families in Greece - Gkaintartzi, Anastasia (Aegean Working Papers in Ethnographic Linguistics, 2025)
This paper outlines a research that aimed to investigate the language repertoires, practices, and ideologies of Serbian-Greek families in Greece. It also attempted to trace family homescapes, focusing on the resources materialising and visibilising the heritage language and culture in the home, in order to understand their role in family language policies. Drawing from the fields of Family Language Policy (FLP) and Linguistic Landscape (LL), 15 semi-structured interviews were conducted with Serbian mothers and children, as well as ‘homescape walking tours’ with the participants. The research data show that language sustenance and the further development of children’s bilingualism/multilingualism is an embedded social process that takes place through spatial and linguistic practices, within their homescapes, which include materialities that are accessible and visible to children and foster the children’s (language, cultural, ethnic) identity formations. The implications of FLP and LL within the Serbian ethnic community, which has a long presence in the country and remains under-researched, are discussed in relation to contemporary urban multilingualism in Greece.